Educação e história em quadrinhos : análise das representações dos jovens do campo no gibi “Chico Bento Moço” - Vaz, Welber Eduardo (2021)
This research has the objective of analyzing the representations of rural youngsters in the comic book Chico Bento Moço, produced by Maurício de Souza Studios. The study gives emphasis to the stereotyped image of these youngsters, mainly present in the speech, the wardrobe and in the ingenuity of the character. Through the analyses, it is investigated the prejudice that the stereotypes associate to the rural youngsters, especially, by migrating to the city in search of Higher Education and better conditions of work, theme of Chico Bento Moço. It addresses the relation between them with the rural environment, their arrival in the city as well as the confrontation related to the accepting and the adapting. In addition, it discusses the experiences of rural youngsters in the university. From this hypothesis that many readers might not know the reality of the diverse culture and knowledge of these people, we problematized the images given in these comic books, based on the Cultural Studies and Cultural Pedagogies. The methodology of this research work is guided by the critical analysis of media, as suggested by Douglas Kellner (2001), who argues that the critical analysis of media enables people conditions to examine it in more autonomous way, being less subject to its suggestions and manipulations. It concluded that these representations are generally stereotyped and that the educational power of the comic book is capable of shaping the thought and the vision of readers in relation to people of the country and may intensify the prejudice and the discrimination against them. But it was also able to notice that this product is renewing its way of representing this population through a different image of the famous stereotype, leading us to question if there was a change in the representation due to considering the diversity of the countryside or to only considering that the city is capable of taking the “countrified” of these people.